Handover Management of Drones in Future Mobile Networks: 6G Technologies - Joana Angjo; Ibraheem Shayea; Mustafa Ergen; Abdulraqeb Alhammadi; Yousef Ibrahim Daradkeh; Hafizal Mohamad (IEEE Xplore, 2024)
Indexed by WOS/Scopus/ERA